166 ZINC DYSHOMEOSTASIS IN RATS WITH ALDOSTERONISM: RESPONSE TO SPIRONOLACTONE. Issue 1 (1st January 2007) - Thomas, M.; Vidal, A.; Bhattacharya, S. K.; Ahokas, R. A.; Sun, Y.; Gerling, I. C.; Weber, K. T.
Abstract : Purpose: Congestive heart failure (CHF) with secondary aldosteronism is accompanied by a systemic illness that includes oxidative stress in diverse tissues. Endogenous antioxidant defenses include intra- and extracellular Cu/Zn-superoxide dismutase (SOD), whose activities are dependent on the bioavailability of Cu and Zn. Hypozincemia occurs in patients with CHF. To elucidate potential mechanisms involved in Zn dyshomeostasis in CHF, we studied Zn balance, its tissue distribution, and plasma and tissue Cu/Zn-SOD activities in rats with aldosteronism. Methods and Results: In rats receiving aldosterone/salt treatment (ALDOST) alone for 1 and 4 weeks or in combination with spironolactone (Spiro), an ALDO receptor antagonist, we monitored 24-hour urinary Zn excretion and tissue Zn levels in heart, liver, and skeletal muscle, together with tissue metallothionein (MT)-I, a Zn-binding protein, NADPH oxidase activation (gp91 phox ), and Cu/Zn-SOD activities in blood and tissues. Compared with untreated, age-/gender-matched controls (mean ± SEM), at days 7 and 28 of ALDOST, we found urinary Zn losses were increased (3.9 ± 0.2 vs 18.9 ± 3.1 and 20.2 ± 2.7 μg/24 h; p < .05), leading to negative Zn balance with hypozincemia (81 ± 3 vs 30 ± 2 and 36 ± 2 μg/dL; p < .05). A fall in plasma Cu/Zn-SOD activity was seen at week 4 (2.29 ± 0.07 vs 1.56 ± 0.11 U/mL; p < .05), together with an atrophy of skeletal muscle myocytes without apoptosis or necrosis and accelerated involution of thymus gland with thymocyte apoptosis (TUNEL assay), another marker of Zn deficiency. Microscopic scars and perivascular fibrosis of intramural coronary arteries first appeared in the right and left ventricles at week 4 ALDOST and were accompanied by gp91 phox activation, increased ( p < .05) tissue Zn (79 ± 5 vs 93 ± 3 ng/mg FFDT), MT-I protein (75 ± 4 vs 123 ± 9 OD), and Cu/Zn-SOD activity (0.56 ± 0.10 vs 0.93 ± 0.12 U/mg protein), which were not found in uninjured liver or skeletal muscle. Spiro cotreatment prevented hyperzincuria (5.6 ± 0.5 μg/24 h), hypozincemia (81 ± 3 μg/dL), Zn dyshomeostasis, cardiac injury, and skeletal muscle wasting. Conclusions: Increased urinary Zn losses, together with Zn preferential translocation to sites of cardiac injury, contribute to Zn dyshomeostasis in rats with aldosteronism, and these responses can be prevented by Spiro. These findings shed light on hypozincemia found in CHF, where neurohormonal activation is present and Spiro cotreatment has proven efficacious.